Adherence to guidelines for antibiotics used in the initial treatment of febrile neutropenia in patients with cancer: a study using health insurance claims database in Japan - Kanako Mizuno; Ryo Inose; Ryota Goto; Yuichi Muraki (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Pseudomonas aeruginosa, a causative microorganism of febrile neutropenia (FN), accounts for approximately 15% of bloodstream infections and is associated with a high mortality rate. Therefore, antibiotics with anti-P. aeruginosa activity should be administered appropriately during the initial treatment of FN. While other countries have examined guideline adherence and its associated factors in FN initial treatment, limited data are available on these aspects in Japan. This study aimed to evaluate adherence to FN treatment guidelines regarding antibiotics used in patients with cancer and identify factors associated with adherence using a Japanese health insurance claims database. Methods This study used the JMDC hospital-based administrative claims database between April 2014 and August 2022 obtained from JMDC Inc. Hospitalized patients with cancer with a definitive diagnosis of FN were included in the study. FN cases were defined as patients who underwent bacteriological culture and identification test for blood in the same month as their first definitive FN diagnosis. The date of the first bacteriological culture and identification test for blood was considered the date of the first FN definitive diagnosis. Results Among 31,947 patients diagnosed with FN, 12,008 underwent bacteriological culture and identification test for blood in the same month as their FN diagnosis. After applying exclusion criteria, 11,292 patients were included in the analysis. The overall adherence rate to FN treatment guidelines for initial antibiotic selection in Japan was 78.8% and remained stable over time, consistently above 75%. Factors significantly associated with guidelines adherence included patients with hematologic malignancies (OR: 1.117, 95% CI: 1.007–1.239). The study also identified trends in antibiotic use in initial treatment. The use of penicillin with beta-lactamase inhibitor significantly increased over time (r = 0.01621, p < 0.001), while carbapenem use significantly decreased (r = -0.00813, p < 0.001). Conclusion The study revealed an FN guideline adherence rate of 78.8% in Japan, along with changes in antibiotic prescribing patterns, including a trend toward carbapenem-sparing strategies between 2014 and 2022. Continuous surveillance is necessary, as adherence rates and antibiotic selection may be influenced by future guideline revisions and antimicrobial stewardship initiatives.